2020
DOI: 10.3389/fpls.2020.01163
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Enhances the Anisotropy of Cell Expansion in the Growth Zone of the Maize Leaf

Abstract: Although plant organ shapes are defined by spatio-temporal variations of directional tissue expansion, this is a little characterized aspect of organ growth regulation. Although it is well known that the plant hormone gibberellin increases the leaf length/with ratio, its effects on cell expansion in the growing leaf are largely unknown. To understand how variations in rate and anisotropy of growth establish the typical monocotelydonous leaf shape, we studied the leaf growth zone of maize (Zea mays) with a kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…R significantly impacts endogenous action of gibberellic acid which is involved in cell elongation, root inhibition, and stimulating mitosis in meristematic cells ( Manivannan et al, 2015 ) for replication. Gibberellic acid action is known to trigger anisotropic responses for leaf expansion in monocots ( Xu et al, 2016 ; Sprangers et al, 2020 ), though R can impart different effects on leaf morphology for different plants in vitro . B increased leaf thickness, leaf numbers and leaf areas compared to R, which reduced leaf thickness and area in cultured Alternanthera brasiliana ( Macedo et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…R significantly impacts endogenous action of gibberellic acid which is involved in cell elongation, root inhibition, and stimulating mitosis in meristematic cells ( Manivannan et al, 2015 ) for replication. Gibberellic acid action is known to trigger anisotropic responses for leaf expansion in monocots ( Xu et al, 2016 ; Sprangers et al, 2020 ), though R can impart different effects on leaf morphology for different plants in vitro . B increased leaf thickness, leaf numbers and leaf areas compared to R, which reduced leaf thickness and area in cultured Alternanthera brasiliana ( Macedo et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In GA-treated plants, the shoots or leaves were significantly elongated, as other studies showed (Fig. S2) (Achard & Genschik, 2009; Xu et al ., 2016; Sprangers et al ., 2020). In addition to promoting plant growth, GA treatment has been reported to induce transcriptional changes (Cheng et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, further exploration is needed to study the regulatory mechanism and function involved in fruit splitting. In addition, gibberellin is a plant hormone that is responsible for promoting cell division and expansion [25,26]. Thus, spraying gibberellin is an important technical measure to increase fruit size, firmness, peel strain and reduce the fruit splitting rate in many woody fruit plants, such as grape (Vitis vinifera) and cherry (Prunus avium) [27,28].…”
Section: Discussionmentioning
confidence: 99%